In Merz we Truss: Financial market reaction to Germany's fiscal package - Filippos Petroulakis; Farzad Saidi (Kiel Institute for the World Economy (IfW Kiel), 2025)
This study analyzes capital market reactions to Germany's recent announcement of loosening fiscal restrictions for defense and state-level spending, while establishing a exteuro500 billion infrastructure investment fund. In particular, we examine whether surging Bund yields reflect growth expectations or fiscal risk concerns. Clear evidence of growth expectations: The steepening German yield curve, rising stock prices, euro appreciation, and stable credit default swap prices collectively indicate that markets interpret Germany's fiscal expansion as growth-enhancing rather than a reckless fiscal bet. The contrast with the UK's Truss-Kwarteng episode is stark: Unlike the 2022 UK "mini budget" aftermath, which triggered a selloff across all UK asset classes, Germany's announcement has seen positive market reception across different asset classes, suggesting confidence in Germany's fiscal credibility. While the policy shift introduces some uncertainty, evidenced by modest increases in the European VSTOXX volatility index, this reaction appears calibrated and partially attributable to concurrent global market events, reinforcing the interpretation that markets view Germany's fiscal expansion as responsible. – – Diese Studie analysiert die Reaktionen der Kapitalmärkte auf Deutschlands jüngste Ankündigung, fiskalische Beschränkungen für Verteidigung und Ausgaben auf Länderebene zu lockern - und gleichzeitig ein 500-Milliarden-Euro-Investitionsfonds für Infrastruktur einzurichten. Insbesondere fragen wir, ob die steigenden Bund-Renditen Wachstumserwartungen oder Risikobedenken widerspiegeln. Klare Evidenz für Wachstumserwartungen: Die steilere deutsche Zinsstrukturkurve, steigende Aktienkurse, die Aufwertung des Euro und stabile Credit-Default-Swap-Preise deuten darauf hin, dass die Märkte Deutschlands fiskalische Expansion eher als wachstumsfördernd denn als fiskalisch bedenklich interpretieren. Der Kontrast zum Truss-Kwarteng-Haushalt im Vereinigten Königreich ist stark: Im Gegensatz zu den Turbulenzen nach dem britischen "Mini-Haushalt" 2022, die einen Ausverkauf über alle UK-Anlageklassen hinweg auslösten, wurde das deutsche Fiskal-Paket von den Märkten über verschiedene Anlageklassen hinweg positiv aufgenommen, was auf Vertrauen in die fiskalische Glaubwürdigkeit Deutschlands hindeutet.
Keywords: 330; Fiscal Policy; Sovereign Debt; Yield Curve; Market Expectations; Debt Brake; Germany; Fiskalpolitik; Staatsverschuldung; Zinsstrukturkurve; Markterwartungen; Schuldenbremse; Deutschland